Millennium Development Goals: The profound research on the Progress of Universal Primary Education in Pakistan (2000-2015) - Siddiqui, Mazhar Ali; Tagar, Hamzo Khan (Archives of Business Research, 2018)
This paper has been written in context of millennium development goal 02 universal primary education for all context. Paper examines millennium development goals (MDGs) period performance with particularly focused on last 05 years performance with expenditure and progress nexus. The qualitative analysis concludes that allocation is increaser sufficiency but its time barred utilizations system with massive mismanagement, investment in security to fight with manic of terrorism and earth quick in norther area of the region hampered millennium development goals agenda at large. The major obstacles in the agenda are sorted out and by the qualitative study and conclude that these obstacles are still prevailing in the system not resolved properly and direly needed to readdress as a challenge before revised strategy of sustainable development goals (SDGs04) quality education for all in Pakistan. Weakened Governance Fragmentation Lack of Clarity in Inter-Tier Relationships Poor Quality of Teachers & Managers Quality of curriculum, textbooks & exams Low level of literacy Out of school children Dropout, In-adequate financing Gender Equity Poor monitoring & evaluation Imbalance in primary, middle & secondary schools inconvenient school locations.